Sustainable Science? Reducing the Carbon Impact of Scientific Mega-Meetings - Alexandra G. Ponette-González; Jarrett E. Byrnes (Ethnobiology Letters, 2011)
Scientists across the globe recognize the importance of reducing carbon emissions to combat climate change.  At the same time, we have increased our carbon footprint through air travel to the growing number of scientific society “mega-meetings” that host thousands of attendees.  Although alternative solutions have been proposed to reduce the environmental impact of annual conferences, these have yet to be evaluated against the business-as-usual scenario.  Here, we use 9 years of annual meeting attendance data from the Ecological Society of America and the Association of American Geographers to assess the efficacy of two additional solutions: 1) alternate large national meetings that require significant air travel with smaller regional meetings that do not; and 2) incorporate geography into the meeting location selection process.  The carbon footprint of annual mega-meetings ranged 3-fold, from 1196-4062 metric tons of CO2.  Results indicate that an alternating schedule of national and regional meetings can reduce conference-related CO2 emissions up to 73%, while improved spatial planning may result in further reductions.  We discuss the benefits and tradeoffs of proposals to green scientific meetings, with a view to spark further debate on how to increase the sustainability of scientific conferences.